2017
DOI: 10.1016/j.quaint.2016.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Human genetic adaptation to high altitudes: Current status and future prospects

Abstract: The question of whether human populations have adapted genetically to high altitude has been of interest since studies began there in the early 1900s. Initially there was debate as to whether genetic adaptation to high altitude has taken place based, in part, on disciplinary orientation and the sources of evidence being considered. Studies centered on short-term responses, termed acclimatization, and the developmental changes occurring across lifetimes. A paradigm shift occurred with the advent of single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 103 publications
1
62
0
Order By: Relevance
“…Studies have shown that maladaptive phenotypes about the circulatory systems that are related to the absorption and delivery of O 2 , such as increases in concentration of hemoglobin and erythrocytes, elevated pulmonary blood pressure (derived from vasoconstriction), and right-ventricle hypertrophy, are ubiquitous in low-altitude mammals when exposed to hypoxia (Tucker and Rhodes, 2001;Storz et al, 2010;Velotta et al, 2018), and low-altitude cattle are hyper-responders to high altitude (Tucker and Rhodes, 2001). Conversely, many high-altitude populations adapt well to hypoxia and exhibit a physiological reaction similar to lowaltitude mammals with normal pulmonary blood pressure, right-ventricle size, and erythrocyte concentration, which can be referred to the effects of selection on genetically based trait variation that suppresses or eliminates these maladaptive phenotypes (Storz et al, 2010;Moore, 2017;Velotta et al, 2018). Hypoxia-inducible factors (HIFs) have been demonstrated to play a central role in the adaptive response to hypoxia by regulating expression of hypoxia-dependent genes that can increase systemic O 2 delivery or improve cellular metabolic adaptation (Semenza, 2000;Covello and Simon, 2004;Taylor, 2008).…”
Section: Cnvs Revealed the Potential Molecular Basis To High-altitudementioning
confidence: 99%
“…Studies have shown that maladaptive phenotypes about the circulatory systems that are related to the absorption and delivery of O 2 , such as increases in concentration of hemoglobin and erythrocytes, elevated pulmonary blood pressure (derived from vasoconstriction), and right-ventricle hypertrophy, are ubiquitous in low-altitude mammals when exposed to hypoxia (Tucker and Rhodes, 2001;Storz et al, 2010;Velotta et al, 2018), and low-altitude cattle are hyper-responders to high altitude (Tucker and Rhodes, 2001). Conversely, many high-altitude populations adapt well to hypoxia and exhibit a physiological reaction similar to lowaltitude mammals with normal pulmonary blood pressure, right-ventricle size, and erythrocyte concentration, which can be referred to the effects of selection on genetically based trait variation that suppresses or eliminates these maladaptive phenotypes (Storz et al, 2010;Moore, 2017;Velotta et al, 2018). Hypoxia-inducible factors (HIFs) have been demonstrated to play a central role in the adaptive response to hypoxia by regulating expression of hypoxia-dependent genes that can increase systemic O 2 delivery or improve cellular metabolic adaptation (Semenza, 2000;Covello and Simon, 2004;Taylor, 2008).…”
Section: Cnvs Revealed the Potential Molecular Basis To High-altitudementioning
confidence: 99%
“…To date, the only mid-MP lithic data set described in detail derives from Qafzeh Cave [14]. Skhul Cave, Tabun layer C as well as Naamé, Nahr Ibrahim, and Ras El-Kelb in Lebanon are the other sites that were mentioned to represent this period [15][16][17][18][19][20][21]. The centripetal assemblages at Qafzeh and Skhul Caves are associated with the remains of H. sapiens [20,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Skhul Cave, Tabun layer C as well as Naamé, Nahr Ibrahim, and Ras El-Kelb in Lebanon are the other sites that were mentioned to represent this period [15][16][17][18][19][20][21]. The centripetal assemblages at Qafzeh and Skhul Caves are associated with the remains of H. sapiens [20,[22][23][24][25]. The rapid accumulation of archaeological evidence from the northeastern Africa, the Arabian Peninsula, and the Levant suggests that early MIS 5 dispersals associated with the centripetal Levallois technology were a well-established phenomenon [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, people who have lived on the plateau for a long time can adapt to such a low-oxygen environment. These people are thought to be more adapted to such an oxygen-deficient environment after years of genetic selection [10,11]. The adaptation e has been speculated to be related to multiple genes.…”
Section: Introductionmentioning
confidence: 99%